PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK TALK WRITE TERHADAP HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS XI SMA NEGERI 1 AMPEK ANGKEK - Zahra, Fadhila (Jurnal Edukasi dan Penelitian Matematika, 2023)
Mathematical learning requires goals. However, UTS results revealed that Class X students at SMA N 1 Ampek Angkek in 2022/2023 had poor mathematics learning outcomes. These maths questions will be solved via TTW cooperative learning. Quasi-experimental research uses non-equivalent post-test only control groups. Study participants were 2023/2024 SMA N 1 Ampek Angkek Class XI students. Simple random sampling selected class. Math learning outcomes test results were analysed using normality, homogeneity, and t-tests. The TTW cooperative learning technique improved maths learning, the research revealed. A t-test rejected H0 at 0.05 with a P-value of 0.020 after data processing. This shows that TTW cooperative learning enhances student learning over direct learning.Keywords– Mathematisc Learning Outcomes, Think Talk Write type Cooperative model